Risks and Opportunities for Central Asian Countries in the Context of New Geopolitics - Fatima Kukeyeva (Journal of Political Science: Bulletin of Yerevan University)
The article analyzes the main risks and opportunities for the Central Asian countries in the context of new geopolitical transformations. In this sense, the geopolitical landscape of Central Asia in the period from 2022 to 2024 is undergoing significant changes that affect regional stability and global interaction. The article examines Central Asia in terms of strategic importance and vulnerability to external pressure, influenced by various global initiatives and changing power dynamics. The countries of the region face a number of risks, such as economic instability, dependence on external energy resources, as well as geopolitical rivalry between major powers, in particular Russia and China. In the context of new geopolitics, it is critical for the Central Asian countries to maintain independence and sovereignty, ensure economic development and strengthen political legitimacy. Despite these challenges, cooperation with international actors and participation in various integration structures can contribute to achieving national interests and minimizing risks. Therefore, the article analyzes the key vectors of the foreign policy of the Central Asian countries, paying special attention to the Russian and Chinese vectors, and considers the opportunities and risks that these countries face in the new geopolitical reality.